Pengaruh Umur Perusahaan, Pertumbuhan Perusahaan, Profitabilitas, Struktur Modal, dan Ukuran Perusahaan Terhadap Nilai Perusahaan - Shabila Siti Salsa; Darya Setia Nugraha (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This research aims to determine the effect of company age, company growth, profitability, capital structure, and company size on company value study in property and real estate companies listed in Indonesia Stock Exchange 2016-2020 period. The sample used in this study consisted of 30 companies listed on the Indonesia Stock Exchange in the property and real estate sector for the 2016-2020 period and selected using the purposive sampling method. The analytical technique used is panel data regression analysis using Eviews 10. The results show that company age, company growth, and company size have a negative effect on company value. Profitability and capital structure have a positive effect on company value. Then simultaneously, company age, company growth, profitability, capital structure, and company size have a positive and significant effect on company value.